PENGARUH LATIHAN SQUAT DAN LEG PRESS TERHADAP STRENGTH DAN HYPERTROPHY OTOT TUNGKAI - Aryadi Rachman (Lambung Mangkurat University, 2014)
Strength is one of the basic components biomotor that is needed in every sport field. In order to achieve optimal performance achievement, then the power should be increased as the underlying basis of the formation of other biomotor components. Exercise increases muscle strength to cope with the load during exercise and the affects muscle hypertrophy. Exercise powers properly implemented will affect the quality and quantity improvement in print sportsmen. The exercise that is used to improve strength and hypertrophy leg muscle is by using weight training method exercise.This study aim to investigate the differences squat exercise and leg press in order to improve strength and hypertrophy leg muscle for student JPOK FKIP UNLAM Banjarbaru class 2011/2012.This type of quantitative research with quasi-experimental methods. The study design using a matching-only design. The population in this study was student JPOK FKIP UNLAM Banjarbaru class 2011/2012 which totaled 40 people, under the provisions of the study sample was 36 people, samples were divided into 3 groups, each group sharing is done through the match subject design. The division is based on the results of the experimental group pretest limb muscle strength using a back and leg dynamometer. Each group numbered 12 people for group I (squats), 12 to group II (leg press exercises) and 12 for the control group.Results of the research: methods squats and leg press exercises significant increase in limb muscle strength and hypertrophy (sig. 0.000 <α = 0.05). Group I, II and III had significant differences (sig. 0.000 <α = 0.05). The average increase in strength for the I =36.16 kg = 26.83 kg II, and III = 3.83 kg. The average increase in muscle hypertrophy for group I = 0.66 cm, II = 0:41 cm, and III = 0:08 cm.Conclusion: there is a significant effect of exercise squats and leg press to increase in leg muscle strength and hypertrophy. Squat exercise greater influence than the leg press and a control group to increase in leg muscle strength and hypertrophy Key words: Squat, leg press, strength and hypertrophy of leg muscle.